Aplicação da técnica de nivelamento de produção em uma unidade de soldagem - Reginato, Tiago (2014)
Lean Production has been much discussed in the industry for the last time its philosophy, concepts and tools apply to different types of production systems. But the big challenge for companies is to break the paradigms of production and tailor them to maturity of companies. Thus the applied research aims to propose the application of the leveling tool on a production welding process with the help of other tools and concepts of lean production to develop a new arrangement for a new plant the company of agricultural implements. Thus for that leveling is properly operated and affected, we used the references found in the literature added knowledge generated through methodologies proposed by the literature and applied in other studies, in which had to be defined a family of products for the necessary indicators, studies as timing and methods and then develop the necessary calculations for the leveling of welding operations. The result obtained a sense of standardization through a structured for workstations with the correct allocation of resources able to meet the demands of variations and create a flow of production and information with a reduced rate of idle line (3 layout, 19%) for 100% demand and, consequently, a high degree of utilization of the line (96.81%), which emphasizes the importance of applying this methodology.